Residual effects of fertilizer application on growth and yield of two cassava varieties in Ibadan, southwestern Nigeria - Edet, M.; Tijani-Eniola, H.; Okechukwu, R.U. (2013)
Field experiments were conducted to investigate the effects of application and residues of organomineral and NPK fertilizers on two cassava varieties in a tropical alfisol in Ibadan, southwestern Nigeria in 2007, 2008 and 2009. Five Organomineral Fertilizer (OF) rates (1.5, 2.5, 3.5, 4.5 and 6.0 t/ha), NPK 15-15-15 at 600 kg/ha and no fertilizer (control) treatments as subplots were evaluated on the performance of TMS 30572 and TMS 92/0326 planted at 10,000 plants per hectare as main plots. Fertilizer was applied at planting using a split plot arrangement in a Randomized Complete Block Design (RCBD) with three replicates. After harvest at 12 Months After Planting (MAP), cassava was replanted in-situ with minimum soil disturbance, without fertilizer application to assess the residual effects of previously applied treatments. Fertilizer application significantly increased cassava root yield but had no significant influence on plant growth parameters and number of storage roots per plant. Yield obtained with NPK application was similar to those obtained with various OF rates. Residues of OF applied at 2.5 to 6.0 t/ha produced yields similar to those of previous application. Fresh and dry root yields of NPK and control treatments were significantly low. The optimum OF rate (2.5 t/ha) is capable of producing optimum cassava root yields in two consecutive cropping seasons.